Construction Of President Joko Widodo's Twitter Account Before And During The Covid-19 Pandemic - Aji, Haryo Kusumo; Sardjono, Herning Suryo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
President Joko Widodo in his second term of government has five visions to achieve, but must face the Covid-19 pandemic which has changed all aspects of the state, including policy directions. Jokowi also uses social media Twitter to provide updates on official state activities through the @jokowi account. For this reason, this research wants to see how the framing or media frames displayed by Joko Widodo's official account before and during the Covid-19 pandemic. The purpose of this research is to see how social media Twitter is constructed in framing President Joko Widodo's policies before and during the Covid-19 pandemic. Is it still in accordance with the five visions of the government in the second period or is it already different. This research constructs President Joko Widodo's social media twitter during the second administration period before and during the pandemic. The method used is qualitative with framing analysis, which concerns how the media interprets, understands and frames the events that are reported. The state of the art of this research is to continue previous research on the framing of President Jokowi's government on YouTube media tempodotco and detikcom. The results of this research are what President Joko Widodo conveyed on his Twitter account before the pandemic focused more on the vision of accelerating infrastructure development, and investing as wide as possible. Meanwhile, during the pandemic, more work was done on the vision of human resource development, bureaucratic reform and the right-target State Budget to tackle Covid-19.